Análisis de la fragmentación de los paisajes altoandinos y su influencia en la percepción hacia los servicios ecosistémicos en la provincia de Tungurahua - Alvarado Sarango, Bertha Nathaly (2024)
High Andean landscapes provide multiple ecosystem services that are vital for millions of highland and lowland inhabitants but are threatened by anthropogenic pressure from land- use change. The objective of the research was to analyze the level of fragmentation of high Andean landscapes in the province of Tungurahua and to determine the social perception of the effects of fragmentation on the provision of ecosystem services (ES) in the landscapes of the canton of Quero. For the fragmentation analysis, metrics were calculated at the class and patch (tessellation) level, and the reticular fragmentation index (RFI) and patch fragmentation index (PFI). The social perception analysis was carried out by applying a survey to heads of households, with a total of 251 respondents. It was recorded for the year 2000, that 44.80% of the tesserae of shrub and herbaceous vegetation were classified as very low RFI, decreasing to 37.32% in 2022. The PFI showed a similar dynamic where 32.98 % of the tesserae were classified in the very low category in 2000 and decreased to 35.80 % in 2022. Participants' perception of ES loss indicated that water service is the most affected, followed by air, pollinating insects and soil, with agriculture and livestock being the main causes. The level of participation in the restoration projects was high, as was the acceptance for future projects.